Canopy, snow, and lichens on woodland caribou range in southeastern Manitoba - Schaefer, James A. (Rangifer, 1996)
I examined the relationships among snow cover (api), lichen abundance, and canopy composition on the range of the Aikens Lake population of woodland caribou (Rangifer tarandus caribou) in southeastern Manitoba. Percent cover of forage lichens (Cladina spp.) was positively correlated with maximum total thickness and with maximum vertical hardness of api. Mixed communities of trembling aspen (Populus tremuloides), spruce (Picea spp.), and balsam fir (Abies balsamea) showed the most favourable nival conditions for caribou but had low lichen abundance; those dominated by jack pine (Pinus banksiana) were the converse. The results suggest an energetic compromise for woodland caribou when foraging for terrestrial lichens. During winter, caribou exhibited significant selection for jack pine communities whereas mixed communities were avoided.